Kinetic Sensitivity of a New Lumbo-Pelvic Model to Variation in Segment Parameter Input - Crewe, H.; Campbell, Amity; Elliott, B; Alderson, J. (Human Kinetics, 2013)
This study aimed to assess variability in lumbo-pelvic forces and moments during a dynamic high-impact activity (cricket fast bowling) when calculated using different body segment parameters (BSPs). The first three BSPs were estimated using methods where the trunk was divided into segments according to nonspinal anatomical landmarks. The final approach defined segment boundaries according to vertebral level. Three-dimensional motion analysis data from nine male cricketers’ bowling trials were processed using the four BSPs. A repeated-measures analysis of variance revealed no significant effect on peak lumbo-pelvic forces. However, the segmentation approach based on vertebral level resulted in significantly larger peak flexion and lateral flexion moments than the other BSP data sets. This has implications for comparisons between studies using different BSP parameters. Further, given that a method defined with reference to vertebral level more closely corresponds with relevant anatomical structures, this approach may more accurately reflect lumbar moments.